2023
DOI: 10.1097/aco.0000000000001233
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in trauma ICUs: a review of incidence, risk factors, outcomes, and management

Abstract: Purpose of reviewThis article reviews the impact and importance of delirium on patients admitted to the ICU after trauma, including the latest work on prevention and treatment of this condition. As the population ages, the incidence of geriatric trauma will continue to increase with a concomitant rise in the patient and healthcare costs of delirium in this population.Recent findingsRecent studies have further defined the risk factors for delirium in the trauma ICU patient population, as well as better demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…In our cohort, prolonged Q1-NE was associated with a higher rate of ICU delirium (59%); this raises a concern about whether our current practices need revising. Delirium rates reported by Williams et al 15 support our findings and add relevance to sys-tematic reviews highlighting the need for ongoing investigation of delirium in neurologically ill patients. 24 The chronological association between prolonged Q1-NE exposure and earlier onset of delirium demonstrates a potential contribution of frequent NEs to the exacerbation of posttraumatic mental status changes due to sleep disruption.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our cohort, prolonged Q1-NE was associated with a higher rate of ICU delirium (59%); this raises a concern about whether our current practices need revising. Delirium rates reported by Williams et al 15 support our findings and add relevance to sys-tematic reviews highlighting the need for ongoing investigation of delirium in neurologically ill patients. 24 The chronological association between prolonged Q1-NE exposure and earlier onset of delirium demonstrates a potential contribution of frequent NEs to the exacerbation of posttraumatic mental status changes due to sleep disruption.…”
Section: Discussionsupporting
confidence: 90%
“…Most patients presented after a fall (90.8%) with median ISS of 14 (10)(11)(12)(13)(14)(15)(16)(17) and head AIS of 3 (IQR, 2-4). Based on our hospital trauma leveling criteria, a minority of patient were trauma activations, Level 1 (8.2%) and Level 2 (33%).…”
Section: Demographics and Injury Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…When pharmacologic strategies are needed, antipsychotic medications (APMs) are commonly prescribed, although their efficacy remains uncertain [17]. Some studies have suggested that APMs may be effective in reducing the duration and severity of delirium symptoms, while others have found no significant benefit [18,19]. The American Geriatrics Society guidelines for the management of delirium recommend the use of antipsychotic medications for patients with severe agitation or distress, but not for the routine treatment of delirium [20].…”
Section: Introductionmentioning
confidence: 99%
“…Delirium is an acute, reversible, widespread cognitive disorder psychotic syndrome characterized by fluctuating disorders of consciousness, inattention, disorganized thinking, or changes in level of consciousness. [ 1 , 2 ] Patients receiving mechanical ventilatory support in the Intensive Care Unit (ICU) are at high risk of delirium. [ 3 ] Delirium can be diagnosed when certain psychiatric symptoms are present without abnormal central nervous system function and organic comorbidities.…”
Section: Introductionmentioning
confidence: 99%